The Effectiveness of Acceptance and Commitment Therapy on Anxiety Sensitivity, Aggression, and Online Shopping Addiction in Adolescents - Sara Malek Mohammadi; Mahtab Shah Hosseini; Narges Asgari Toorzani; Farzin Bagheri Sheykhangafshe; Abbas Ali Hossein Khanzadeh (Caspian Journal of Health Research)
Background: Social Media Disorder (SMD) is a growing behavioral addiction among adolescents, marked by excessive and uncontrolled use of social media. It is associated with emotional difficulties such as anxiety, aggression, and impulsive behaviors, including online shopping addiction (OSA). Objectives: This study examined the effectiveness of Acceptance and Commitment Therapy (ACT) in reducing anxiety sensitivity, aggression, and OSA in adolescents with SMD. Materials and Methods: A randomized controlled clinical trial was conducted using a pretest-posttest design with a control group. Thirty-six adolescents with SMD were purposively recruited from secondary schools in Tehran’s District 8 and randomly assigned to an experimental group (n = 18) or a control group (n = 18). The experimental group received eight weekly 90-minute ACT sessions; the control group received no intervention. Data were collected using the Social Media Disorder Scale (SMDS), Anxiety Sensitivity Index-3 (ASI-3), Buss and Perry Aggression Questionnaire (BPAQ), and Online Shopping Addiction Scale (OSAS). Data were analyzed using multivariate analysis of covariance in SPSS-27. Results: ACT significantly decreased anxiety sensitivity (F=63.67, P=0.001, η2=0.68), aggression (F=62.66, P=0.001, η2=0.66), and OSA (F=46.17, P=0.001, η2=0.59), in adolescents with SMD (P<0.01). Conclusion: ACT is an effective intervention for reducing emotional dysregulation and compulsive behaviors among adolescents with SMD. These findings suggest its broader utility in addressing psychological challenges linked to digital overuse in youth populations.